Genomic analysis of Neisseria elongata isolate from a patient with infective endocarditis - Marcos André Schörner; Hemanoel Passarelli‐Araujo; Mara Cristina Scheffer; Fernando Hartmann Barazzetti; Jessica Motta Martins; Hanalydia deMelo Machado; Jussara Kasuko Palmeiro; Maria Luiza Bazzo (FEBS Open Bio, 2021)
Neisseria elongata is part of the commensal microbiota of the oropharynx. Although it is not considered pathogenic to humans, N. elongata has been implicated in several cases of infective endocarditis (IE). Here, we report a case of IE caused by N. elongata subsp. nitroreducens (Nel_M001) and compare its genome with 17 N. elongata genomes available in GenBank. We also evaluated resistance and virulence profiles with Comprehensive Antibiotic Resistance and Virulence Finder databases. The results showed a wide diversity among N. elongata isolates. Based on the pangenome cumulative curve, we demonstrate that N. elongata has an open pangenome. We found several different resistance genes, mainly associated with antibiotic efflux pumps. A wide range of virulence genes was observed, predominantly pilus formation genes. Nel_M001 was the only isolate to present two copies of some pilus genes and not present nspA gene. Together, our results provide insights into how this commensal microorganism can cause IE and may assist further biological investigations on nonpathogenic Neisseria spp. Case reporting and pangenome analyses are critical for enhancing our understanding of IE pathogenesis, as well as for alerting physicians and microbiologists to enable rapid identification and treatment to avoid unfavorable outcomes.